Species - Mancuso, Frank Jr.; Feldman, Dennis; Kingsley, Ben; Madsen, Michael; Molina, Alfred; Whitaker, Forest; Helgenberger, Marg; Henstridge, Natasha; Donaldson, Roger; Egerton, Mark; Streit, David; Geiger, H.R.; et al. (Santa Monica, California Metro-Goldwyn-Mayer home entertainment, 1995)
When a creature genetically engineered through extraterrestrial intelligence escapes from observation, scientist Xavier Fitch assembles an elite team of experts to track it down. These experts--a government assassin, an "empath", a biologist and an anthropologist combine their expertise and trace their prey to Los Angeles. There, in the form of a stunning young woman, the alien initiates a horrific plan: to mate with unsuspecting men and produce offspring that could destroy mankind. As her deadly biological clock ticks rapidly, Fitch and his team are hurled into a pulse-pounding chase in which the fate of humanity itself hangs in the balance.
Starring Ben Kingsley, Michael Madsen, Alfred Molina, Forest Whitaker, Marg Helgenberger, Natasha Henstridge.
Dolby Digital, surround.
Printed and exclusively distributed in the Philippines by Viva Video, Inc.
Keywords: Science fiction films